Los derechos humanos y la responsabilidad del Estado - Maraniello, Patricio (2023)
People who cause damage to others by their own acts are, in principle, liable for such conduct and must repair the damage they have caused. As a subject of law, the state is also liable, with certain peculiarities. The responsibility of the state for viola tion of human rights is linked to its double role as protector, since it must not enact rules that restrict or destroy fundamental rights, and neither can it act in clear violation of the constitutional parameters. Argentina has gone through two major peri ods in recent times: that of de facto governments and that of democratic governments. In the second of these periods, the state did often behave arbitrarily, but it differed from the previous period in that it created standards that have allowed victims to be compensated. This protection has been extended through the incorporation of international human rights treaties.